2020
DOI: 10.3390/ijms21249521
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dysfunctions of Mitochondria-Associated Membranes (MAMs) in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a multifactorial neurodegenerative pathology characterized by a progressive decline of cognitive functions. Alteration of various signaling cascades affecting distinct subcellular compartment functions and their communication likely contribute to AD progression. Among others, the alteration of the physical association between the endoplasmic reticulum (ER) and mitochondria, also referred as mitochondria-associated membranes (MAMs), impacts various cellular housekeeping functions suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 235 publications
(200 reference statements)
0
32
0
1
Order By: Relevance
“…In controlling the intracellular Ca 2+ concentrations, mitochondria interact with the ER through mitochondria-associated ER membranes (MAMs) [ 73 ], microdomains where the OMM is just 10–100 nanometers apart from the ER [ 74 , 75 ]. These areas are enriched in inositol 1,4,5-triphosphate receptors (IP3Rs) [ 76 ] which form functional complexes with VDACs through a chaperone, Grp75 (glucose-regulated protein 75), belonging to the heat shock protein 70 family [ 77 ].…”
Section: Mitochondria In the Brainmentioning
confidence: 99%
“…In controlling the intracellular Ca 2+ concentrations, mitochondria interact with the ER through mitochondria-associated ER membranes (MAMs) [ 73 ], microdomains where the OMM is just 10–100 nanometers apart from the ER [ 74 , 75 ]. These areas are enriched in inositol 1,4,5-triphosphate receptors (IP3Rs) [ 76 ] which form functional complexes with VDACs through a chaperone, Grp75 (glucose-regulated protein 75), belonging to the heat shock protein 70 family [ 77 ].…”
Section: Mitochondria In the Brainmentioning
confidence: 99%
“…The ER-mitochondria contacts are also involved in the ER stress-mediated cell death and UPR, because several ER co-factors and chaperones are present at MAM. Moreover, impairment in the UPR, apoptosis, and misfolded proteins accumulation are common features of AD [ 87 ]. In the early phase of ER stress, the cell adapts to stressful conditions through the increase of ER-mitochondria connection, which facilitates mitochondrial Ca 2+ uptake and ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40–44 ] For example, MAMs structure alteration involved in pathophysiological process of Alzheimer's disease, so authors assumed that MAMs should constitute a new therapeutic target in AD. [ 45 ] Another study showed that MAMs disorder participated in hepatic insulin resistance of type 2 diabetic rats. [ 46 ] In our study, DIO improved Ca 2+ homeostasis and MAM structure greatly.…”
Section: Discussionmentioning
confidence: 99%